2016
DOI: 10.1038/srep26125
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide drug screening using mass spectrometric imaging of bead-arrays

Abstract: A fundamental challenge in the drug discovery process is to develop compounds with high efficacy and minimal side-effects. We describe a new approach to proteome-wide drug screening for detection of on- and off-target binding which combines the advantages of mass spectrometry with microarray technology. The method involves matrix-assisted laser desorption/ionization mass spectrometric imaging (MALDI-MSI) of agarose micro-beads randomly arrayed at high-density in custom micro-well plates. Each bead carries a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It should also be noted that we, like others, have mostly considered CNS targets as being responsible for the clinical trial accident and serine hydrolases in particular. Although our study in SHRSP was carried out to explore possible mechanisms outside the CNS (albeit related to CNS vasculature), further studies outside the CNS and looking more broadly at protein targets using proteome‐wide screening techniques, such as surface plasmon resonance or MS imaging (Yang et al, ; Zhou, Liu, Rothschild, & Lim, ) could be of relevance. One other aspect that needs to be considered is that in this study and most of the non‐clinical studies with BIA 10‐2474, the rats were relatively young, although at the end of the 26‐week toxicology study, they would correspond to 25‐ to 30‐year‐old humans according to Sengupta () and no pathology of the type seen in the clinic was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that we, like others, have mostly considered CNS targets as being responsible for the clinical trial accident and serine hydrolases in particular. Although our study in SHRSP was carried out to explore possible mechanisms outside the CNS (albeit related to CNS vasculature), further studies outside the CNS and looking more broadly at protein targets using proteome‐wide screening techniques, such as surface plasmon resonance or MS imaging (Yang et al, ; Zhou, Liu, Rothschild, & Lim, ) could be of relevance. One other aspect that needs to be considered is that in this study and most of the non‐clinical studies with BIA 10‐2474, the rats were relatively young, although at the end of the 26‐week toxicology study, they would correspond to 25‐ to 30‐year‐old humans according to Sengupta () and no pathology of the type seen in the clinic was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In our approach, we apply the advantage of the high-throughput scanning capability of MALDI MS to measure Affi-BAMS' microarrays containing thousands of spots of bead-captured analytes. The microarrays are produced on standard-size microscope slides that fit the majority of current MALDI MS instruments and have flat surfaces, thereby eliminating the need for orthogonal laser beam geometry, which is a prerequisite for probing arrays of microwells [74].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, brigatinib inhibits various fibroblast growth factor receptors (FGFRs), several EPH receptors, and non-RTKs at low micromolar concentrations that have been achieved clinically by many other RTK inhibitors. Using a proteome-wide drug screening approach, it was confirmed that brigatinib strongly interacts with ALK, PTK2/FAK1, and PTK2B/FAK2 and has a medium affinity to IGF-1R and EGFR [20]. These results suggest that the non-RTKs FAK/PTK2 and FER, which are strongly inhibited by brigatinib in NF2-deficient meningioma and schwannoma cells, are important for the growth and survival of these tumors.…”
Section: Plos Onementioning
confidence: 85%